Eyelid dermatitis caused by allergic contact to acrylates in artificial nails (Dermatology Reports, 2017)
Over the past few years, there has been an increase in cases of allergic contact dermatitis caused by acrylates, because of the growing popularity of artificial nails. Pathological reactions to artificial nails typically occur on or around the nail area. Eyelid contact dermatitis due to artificial nails is rarely seen, especially in a nonoccupational setting. The authors report the case of a 45-year-old female accountant who developed eyelid dermatitis due to artificial nails.